S137 Understanding the mechanisms for the increased prevalence of gastro-oesophageal reflux in cystic fibrosis. (December 2018) - Lord, RW; Casey, J; Houghton, LA; Treadway, S; Jones, R; Barry, PJ; Whorwell, PJ; Smith, JA; Jones, AM
Abstract : Objectives: There is as yet no widely accepted explanation for the increased prevalence of gastro-oesophageal reflux seen in CF populations. It is believed that increased reflux may negatively affect CF lung disease, possibly as a consequence of reflux aspiration. However at present treatments are limited to acid suppression and surgery. We aim to investigate the mechanisms responsible for the increased reflux, which may in turn help develop further therapeutic strategies. Methods: We have conducted a prospective observational study in stable adult CF patients, measuring reflux with combined pH and impedance (pH-MII). High resolution manometry (HRM) assessed for a hiatus hernia, OGJ hypotension and oesophageal dysmotility, all of which have been linked to increased reflux. Where appropriate the impact of these on measures of reflux was assessed. Differences between groups were tested with a Mann-Whitney analysis and correlations with a Spearman rank. Results: 41 patients were recruited with 39 patients (mean age 31 years, mean FEV1 52% predicted, 30 males) completing all measures. HRM only detected a hiatus hernia pattern in 4/39. Using resting lower oesophageal sphincter (LOS) pressure, the conventional measure for OGJ dysfunction (normal value >10 mmHg), 6/39 had hypotension. Whereas using the OGJ-Contractile integral (OGJ-CI), a measures of contractility, the majority (27/39) had hypocontractility as determined by a value below 38.5 mmHg.cm. Oesophageal dysmotility was noted in 26/39 using the Chicago Classification v3 (21 impaired oesophageal motility, 4 absent contractility and 1 oesophageal spasm). The resting LOS pressure correlated (rs =−0.371, p=0.024) and the OGJ-CI showed a trend toward correlation (rs =−0.274, p=0.101) with total acid exposure. There was no suggestion of correlations with other reflux measures. Oesophageal dysmotility did not correlate with any reflux measure. Conclusion: We have shown that OGJ dysfunction, occurring mainly without a hiatus hernia, and oesophageal dysmotility are highly prevalent in CF. Our results suggest that OGJ dysfunction is likely an important factor in generation of increased acid exposure. Given the lack of hiatus hernia, it is possible that the OGJ dysfunction is a direct consequence of CFTR dysfunction and its action on muscle. As such CFTR modulation maybe a potential therapeutic option for increased reflux.